The Moderating Effect of Education Level and Income on Job Performance of Supervising Engineers - Ali Katebi; Ahmadreza Keshtkar-Ghalati; Bahareh Katebi; Zahra Alsadat Ardestani; Ali Bordbar (Buildings)
The proper implementation of the monitoring process in construction projects helps strengthen sustainable development indicators. The aim of this study is to investigate the moderating effects of education and income on the relationship between job performance and effective factors on supervising engineers. Data gathering was performed by questionnaire, and analysis was performed with the PLS-SEM approach. According to the results of the moderator analysis, demographic variables of education and income levels, on the relationship between feedback and competence, as well as the relationship between job identity and job performance, had a significant moderating role. In addition, the moderating effect of demographic variables on the relationship between autonomy and competence, as well as the relationship between affective commitment and job performance, was confirmed. The moderating effect of income demographic variables on the relationship between independence and affective commitment and the relationship between competence and job performance was meaningful. To achieve a better understanding of the effects of variables on job performance, the mediation role of competence and affective commitment was studied in the research model. By using the results of this research, officials and managers of construction organizations can adopt appropriate payment and training policies, to better management of the performance of the supervising engineers.